Study Neo-Hookean and Yeoh Hyper-Elastic Models in Dielectric Elastomer-Based Micro-Beam Resonators - Saeed Danaee Barforooshi; Ardeshir Karami Mohammadi (Latin American Journal of Solids and Structures)
Abstract Micro-bridge resonator with dielectric elastomer that is sandwiched between two electrodes is studied here with geometric and material nonlinearity. Geometric nonlinearity is introduced with Von-Karman strain-displacement relationship. For material nonlinearity that is modeled rarely in articles, two hyper-elastic models are used here. Governing equation of motion for Neo-Hookean and Yeoh models are derived through Hamilton's principle. These equations show that Neo-Hookean is not a suitable model for this case because of inadequate terms, but the Yeoh one is. Governing equation in Yeoh model is solved by analytical Lindstedt-Poincare method. Time history of micro-beam is presented in different modes and it is shown good agreement with numerical method. It is seen that increasing of mode number leads to increasing of frequency. In addition, the influence of different parameters on nonlinear normalized frequency is illustrated.